How to deliver integrated care : a guidebook for managers - Kaehne, Axel, 1971-; Nies, Henk (Emerald Publishing Limited, 2021)
Care integration has become an important part of managing health and social care services all over the world. Bringing organisations together is thought to produce better access to care, reduce health care expenditure and improve quality of care for patients and service users. This book helps managers to think about how to collaborate in integrated care programmes. It provides practical advice on how to implement various aspects of care integration, such as fice, digital technology and evaluation. The book also contains chapters on the social and behavioural strategies, values and leadership approaches that should underpin integration. Each chapter contains key information based on the current state of research, illustrations from practical contexts and further reading.
Includes index.
Keywords: Health services administration.; Medical -- Administration.; Medical administration & management.; elektronické knihy; electronic books